Varietal response of chickpea (Cicer arietinum L.) towards the allelopathy of different weeds - Khan, Rahamdad; Khan, Ijaz Ahmad (Universiti Kebangsaan Malaysia, 2015)
In a laboratory trial three chickpea varieties viz, Karak-I, Karak-III and Shenghar were tested against the phytotoxicity of five weed species: Parthenium hysterophorus L., Phragmites australis (Cav.) Trin., Datura alba L., Cyperus rotundus L. and Convolvulus arvensis L. in January 2013. The weed extracts were prepared at the rate of 120 g/L (w/v) after shade dry. The results indicated highly significant inhibitory effect of all the tested weed species on the chickpea varieties. The results also showed that the chickpea variety Karak-III was more susceptible to the phytotoxcity of the tested weed extracts. Among the extract, C. arvensis proved much toxic in term of inhibition of germination by giving only 43.33% germination in comparison with control where 97.50% germination was recorded. On the other hand, the effect of P. australis extract was found a little stimulator by speeding the seed germination in all varieties and giving a low (2.21) mean germination time (MGT) value. From the current results it can be concluded that the infestation of C. arvensis can pollute the soil by accumulating toxic chemicals that leads to the germination failure and growth suppression in chickpea. Therefore, the prevention and removal of C. arvensis in the chickpea growing areas could be recommended. In addition, P. australis must be tested against chickpea weeds (chickpea varieties withstand against its phytotoxcity), so that it can be popularized as bioherbicide in chickpea if it gave promising results in controlling chickpea weeds.